An Opportunistic Directional MAC Protocol with Pulse/Tone Exchange in Wireless Ad-Hoc Networks - Okazawa, Tetsuro; Ma, Jing; Komuro, Nobuyoshi; Choi, Youngjune; Li, Zhetao; Pei, Tingrui; Sekiya, Hiroo (Wireless Personal Communications, 2020)
This paper proposes a Medium Access Control (MAC) protocol using directional antennas in wireless ad-hoc networks, which achieves frame-collision reduction, freezing-state duration reduction, and deafness-problem mitigation simultaneously. The idea of the proposed protocol is that Pulse/Tone exchange is applied to the Opportunistic Directional MAC protocol (OPDMAC). By applying the Pulse/Tone exchange prior to Request to Send/Clear to Send (RTS/CTS) handshake, RTS-to-RTS frame collisions are reduced dramatically. Additionally, RTS-to-DATA frame collisions in the OPDMAC are changed to Pulse signal-to-DATA frame overlaps in the proposed protocol. This change makes the DATA-frame transmissions in success because the Pulse signal-to-DATA frame overlaps are regarded as a deafness problem. On that basis, the deafness-problem mitigation can be obtained in the proposed protocol by adaptive transmission-direction switching, which follows the OPDMAC technique. The freezing-state durations can be also reduced by the transmission-direction switching. As a result, the proposed protocol provides high network throughput compared with conventional protocols. Simulation results show the validity and effectiveness of the proposed protocol.
Keywords: Deafness problem; Directional Antenna; Hidden node problems; MAC protocol; Narrowband signal; Ad hoc networks; Deafness problem; Directional antennas; Hidden-node problem; MAC protocol; Narrow band signal